1974
DOI: 10.1111/j.1095-8649.1974.tb04543.x
|View full text |Cite
|
Sign up to set email alerts
|

A population study of Barbus barbus (L.) in the River Severn, England

Abstract: The results of the application of Schnabel (Chapman modification), Schumacher & Eschmeyer, Fisher & Ford, and Jolly capture-recapture techniques on the Burbus burbus (L.) population in four areas of the middle Severn are compared. The survival of tagged fish varied in different areas and fish released in some time periods were less vulnerable to recapture than fish released from other samples. It is suggested that the shoaling behaviour of Burbus barbus resulted in non-random mixing of marked fish. The average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…When the populations were grouped according to their indigenous and nonindigenous ranges, there □ River Dunajec, Poland; ○ River Warta, Poland; River l'Allier, France (Hunt & Jones 1975;Przybylski et al 2004;Prokes et al 2006;Fishbase 2012); the solid line represents the growth curves for all rivers in this study as modelled by the log -log quadratic function of Vilizzi & Walker (1999) (cf. When the populations were grouped according to their indigenous and nonindigenous ranges, there □ River Dunajec, Poland; ○ River Warta, Poland; River l'Allier, France (Hunt & Jones 1975;Przybylski et al 2004;Prokes et al 2006;Fishbase 2012); the solid line represents the growth curves for all rivers in this study as modelled by the log -log quadratic function of Vilizzi & Walker (1999) (cf.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the populations were grouped according to their indigenous and nonindigenous ranges, there □ River Dunajec, Poland; ○ River Warta, Poland; River l'Allier, France (Hunt & Jones 1975;Przybylski et al 2004;Prokes et al 2006;Fishbase 2012); the solid line represents the growth curves for all rivers in this study as modelled by the log -log quadratic function of Vilizzi & Walker (1999) (cf. When the populations were grouped according to their indigenous and nonindigenous ranges, there □ River Dunajec, Poland; ○ River Warta, Poland; River l'Allier, France (Hunt & Jones 1975;Przybylski et al 2004;Prokes et al 2006;Fishbase 2012); the solid line represents the growth curves for all rivers in this study as modelled by the log -log quadratic function of Vilizzi & Walker (1999) (cf.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that growth rates and lengths in females can be greater than in males (Hunt & Jones 1975). During these assessments, a total of 2358 sites of 100 m length were fished in 202 rivers across a 3-year cycle (i.e., each site was fished, on average, three times in the study period) using DC electric fishing (hand-held or boat-mounted) and seine netting (as appropriate for the habitat).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structuring of the population in groups of genetically related individuals may amplify, by sampling effect, small fluctuations of completely random origin. Unfortunately, the statistical analysis of the only study suggesting shoaling behaviour ( Hunt & Jones, 1974a) was not carried out in such a way as to answer this question unambiguously. However, in our fishing campaigns, we commonly observed that, in winter, individuals were clustered in the river, and clusters seemed to be composed of morphologically similar individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty of estimating the actual size offish populations in fresh waters remains an outstanding problem, particularly in large water bodies (Brown 1975;O'Hara 1981). Mark-recapture estimates are often time-consuming and have frequently produced results of dubious validity, especially when the underlying assumptions of the various models have not been fulfilled (Matthews 1971;Hunt & Jones 1974;Begon 1979). An alternative approach, and one which has found favour in water bodies where areas can be delineated and effectively closed, is that of a removal technique, using either a series of nettings or electrofishings to capture the fish.…”
Section: Introductionmentioning
confidence: 99%